Shifting the Culture Around Public Health Advocacy: Training Future Public Health Professionals to Be Effective Agents of Change. Issue 6 (November 2017) - Blenner, Sarah R.; Lang, Cathy M.; Prelip, Michael L.
There is a critical need to build the capacity of our current and future public health workforce and the communities we serve to engage in public health advocacy. Advocacy should be an integral piece of our intervention strategies and public health discourse. Incorporating public health advocacy into public health training, practice, and research serves as a long-term investment for the public's health. Advocacy can achieve systemic change by addressing the social determinants of health. We developed an advocacy training program that embeds students in community-based organizations (CBOs) for 9 months, providing students with experiential education through the application of advocacy skills and CBOs with opportunities to expand and broaden their advocacy efforts. We have three priority populations: graduate students, CBOs serving Los Angeles County, and the broader Los Angeles County community, focusing on vulnerable populations. Our multifaceted approach addresses the necessity of public health advocacy among the health professions. Through changing how we train students and how communities and universities collaborate, we can strengthen the public health workforce and build healthier communities.